A method for preparing hydrophilic polyester melt-blown nonwoven fabric
By using coated modified inorganic nanofunctional powders in polyester meltblown nonwovens, the problem of difficult to take into account both melt index and hydrophilicity in the prior art is solved, and higher mechanical and hydrophilic properties are achieved.
Patent Information
- Application Number
- CN202510194236.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The melt index and hydrophilicity of existing polyester meltblown nonwovens are difficult to take into account, which affects its application and hydrophilic properties in high load environments.
The melt index and hydrophilicity of polyester meltblown nonwovens are used to coat modified inorganic nanofunctional powders, including coupling agent modified inorganic nanopowders and hydrophilic hyperbranched polyester, and the melt index and hydrophilicity of polyester meltblown nonwovens are improved through blending and hot air traction technology.
The melt index and hydrophilicity of polyester meltblown nonwovens are improved, the drafting and crystallization orientation of the fibers are enhanced, and its mechanical properties and water molecules adsorption ability under high loads are improved.
Smart Images

Figure CN119686023B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of melt-blown nonwoven fabrics and relates to a method for preparing a hydrophilic polyester melt-blown nonwoven fabric. Background Art
[0002] Nonwoven fabrics have good sound absorption, heat insulation, shielding, etc., and are widely used in the fields of medical care, heat preservation, sound absorption, filtration, etc. In addition, different raw materials used in nonwoven fabrics will also give nonwoven fabrics different properties. In particular, meltblown nonwoven fabrics have the characteristics of small pore size and high porosity, so they have unique advantages in the field of filtration and can be used in air filtration, liquid filtration, etc.
[0003] The raw materials of meltblown nonwovens are mostly typical hydrophobic polypropylene (PP), which leads to poor hydrophilicity of meltblown nonwovens. Further hydrophilic treatment is often required for the prepared meltblown fabrics. At the same time, the mechanical properties of PP meltblown fabrics are relatively low, which largely limits their application in certain fields. Polyethylene terephthalate (PET, polyester) has a high melting point. Compared with olefins, meltblown nonwovens made of it have higher mechanical strength and can meet the application in high-load environments. This polyester meltblown nonwoven has a broad market. Therefore, it is of great significance to study polyester meltblown nonwovens.
[0004] With the development of polyester meltblown nonwovens in the field of materials, the development of hydrophilic polyester meltblown nonwovens has also become an important branch of the meltblown field. At present, there are two main aspects to improve the hydrophilicity of polyester meltblown nonwovens:
[0005] One is to improve the hydrophilicity of the surface of meltblown nonwovens through post-treatment technology, such as impregnation. This post-treatment hydrophilicity improvement technology aims to improve the moisture and water absorption capacity of the fiber without significantly changing the original properties of the fiber, thereby enhancing the hydrophilicity of the fiber surface. Common post-treatment methods mainly include adsorption and film-forming technology of hydrophilic finishing agents and surface grafting polymerization technology, but these post-treatment processes are relatively complex, with high production costs, and are difficult to promote and apply in large quantities and on a wide range.
[0006] Second, hydrophilic substances are mixed into the melt-blown spinning process to give the melt-blown nonwoven fabric hydrophilicity. For example, patent application CN114381860A discloses a method for making a hydrophilic PET melt-blown material, using 100 parts by weight of PET, 3-9 parts by weight of polyethylene glycol, and 1-5 parts by weight of silicon dioxide with a particle size of less than 100 nanometers as raw materials, first pre-mixing the polyethylene glycol and silicon dioxide to form a mixture, then adding the mixture and PET to a twin-screw extruder for blending and melting to form a melt, and finally sending the melt to the melt-blown die head, spraying it through the spinneret of the melt-blown die head, cooling, forming a net, and forming a melt-blown cloth. This method changes the melt index of PET by adding polyethylene glycol, and improves the hydrophilicity of PET by adding silicon dioxide. However, if there is too much silicon dioxide, the melt index will be affected, and if there is too little silicon dioxide, it is difficult to effectively improve the hydrophilicity of the melt-blown nonwoven fabric, and it is difficult to take into account both the melt index and the hydrophilicity.
[0007] Therefore, in view of the problem that the melt index and hydrophilicity are difficult to take into account in the prior art, it is necessary to develop a new hydrophilic polyester meltblown nonwoven fabric. Summary of the invention
[0008] The purpose of the present invention is to solve the above problems existing in the prior art and provide a method for preparing a hydrophilic polyester melt-blown nonwoven fabric.
[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing a hydrophilic polyester melt-blown nonwoven fabric, the process flow is: raw material drying → melt spinning → hot air traction → roller receiving and forming;
[0011] The raw material contains 8-10wt% of coated modified inorganic nano functional powder, and the base material of the raw material is polyester;
[0012] The coated modified inorganic nano functional powder includes a coupling agent modified inorganic nano powder and a hydrophilic hyperbranched polyester coated on the surface thereof. The function of the inorganic nano powder is to improve the hydrophilicity of the polyester substrate. The coupling agent modified inorganic nano powder contains an amino group or an epoxy group. The purpose of modifying the inorganic nano powder with a coupling agent is to introduce an amino group or an epoxy group on the surface of the inorganic nano powder. The hydrophilic hyperbranched polyester contains a sulfonic acid group. The sulfonic acid group on the surface of the hydrophilic hyperbranched polyester and the amino group or epoxy group on the surface of the coupling agent modified inorganic nano powder act through ionic bonds or hydrogen bonds to achieve the coating of the coupling agent modified inorganic nano powder by the hydrophilic hyperbranched polyester. The inorganic nano powder is one of zinc oxide nano powder, silicon dioxide nano powder and titanium dioxide nano powder.
[0013] The D50 particle size (i.e. median diameter or median particle size) of the coated modified inorganic nano-functional powder is 80-150nm;
[0014] The preparation process of the coated modified inorganic nano functional powder is as follows: the hydrophilic hyperbranched polyester and the coupling agent modified inorganic nano powder are reacted at a temperature of 140-160° C. and a stirring speed of 2000-3000 rpm for 1-2 hours to obtain the coated modified inorganic nano functional powder; wherein the mass ratio of the hydrophilic hyperbranched polyester to the coupling agent modified inorganic nano powder is 1:(1-3);
[0015] During hot air drawing, the hot air temperature is 330-350℃ and the drawing air pressure is 0.1-0.3MPa;
[0016] The fiber diameter range of hydrophilic polyester meltblown nonwovens is 1-5 μm, with an average diameter of 2-3 μm;
[0017] The polyester substrate prepared by the present invention has a high melt index, and the prepared polyester melt-blown nonwoven fabric has excellent hydrophilicity, because after the coated modified inorganic nano-functional powder is compounded with the polyester substrate, during the melt spinning process, the hydrophilic hyperbranched polyester in the melt state greatly improves the melt index of the polyester substrate, improves the fluidity of the polyester substrate, promotes the melt to be fully drawn under the action of hot air traction, and obtains a polyester melt-blown nonwoven fabric with a smaller fiber diameter, and the added amount of the coated modified inorganic nano-functional powder with a specific particle size is high, and a large number of protrusions can be formed on the surface of the fiber after full drawing, and a large number of grooves are formed between the protrusions on the same fiber surface, which is conducive to the rapid flow of water on the fiber surface. Spreading, a large number of capillary-like channels are formed between the protrusions of different fibers, which is conducive to the rapid conduction of water and enhances the hydrophilicity and moisture conductivity of the polyester melt-blown nonwoven fabric; the drying temperature and time, the temperature of the melt spinning and the receiving distance during the receiving molding have no effect on the fiber diameter, and thus will not affect the formation of a large number of protrusions on the fiber surface by the coated modified inorganic nano-functional powder of a specific particle size; at the same time, the sulfonic acid group in the hydrophilic hyperbranched polyester is extremely hydrophilic, which can improve the hydrophilicity of the polyester melt-blown nonwoven fabric. When the fiber diameter is small, more sulfonic acid groups will be distributed on the fiber surface, further enhancing the adsorption of water molecules on the fiber surface and improving the hydrophilicity of the polyester melt-blown nonwoven fabric.
[0018] As the preferred technical solution:
[0019] The preparation method of the hydrophilic polyester melt-blown nonwoven fabric as described above, the preparation steps of the hydrophilic hyperbranched polyester are as follows:
[0020] (a) adding polyol, polyacid and catalyst 4-methylbenzenesulfonic acid into a reaction kettle, reacting at 140-160° C. for 3-5 hours under the protection of nitrogen or inert gas, accompanied by stirring during the reaction, and the stirring speed is 300-600 r / min, to obtain hyperbranched polyester through polycondensation reaction of polyacid and polyol;
[0021] (b) adding sodium dimethyl 5-sulfonate isophthalate to the reaction kettle and continuing the reaction for 1-2 hours to connect the periphery of the hyperbranched polyester with highly hydrophilic sulfonic acid groups through ester exchange reaction;
[0022] (c) After cooling to 100-120° C., continuously evacuate (control the vacuum degree in the reactor to be less than 80 Pa) for 0.5-1 h to remove the unreacted raw materials in the reactor, and perform post-treatment (discharging, cooling, and crushing) to obtain a hydrophilic hyperbranched polyester;
[0023] The polyol is one of pentaerythritol, glycerol, 3,5-dihydroxytoluene, 1,1,1-trimethylolpropane or tris(hydroxyethyl)isocyanurate;
[0024] The polyacid is one or two of 2-hydroxysuccinic acid, phenylmalonic acid, phthalic acid, phthalic anhydride, 9,10-dihydro-9-oxa-10-phosphophananthrene-succinic acid or 2-carboxyethylphenylphosphinic acid;
[0025] The molar ratio of the polyol, the polyacid, the sodium dimethyl 5-sulfonate of isophthalate and the catalyst 4-methylbenzenesulfonic acid is 1:(1.05-1.20):(0.2-0.4):(0.001-0.003).
[0026] The preparation method of the hydrophilic polyester melt-blown nonwoven fabric as described above, the preparation process of the coupling agent modified inorganic nano powder is: adding the coupling agent and the inorganic nano powder into a high-speed blender with a rotation speed of 2500-3000 r / min, reacting at 80-100° C. for 2-3 hours, and obtaining the coupling agent modified inorganic nano powder;
[0027] The mass of the coupling agent is 3-5% of the mass of the inorganic nano powder, and the coupling agent is one of gamma-aminopropyl triethoxysilane, gamma-aminopropyl trimethoxysilane or 3-glycidyloxypropyl triethoxysilane.
[0028] The method for preparing a hydrophilic polyester melt-blown nonwoven fabric as described above, wherein the raw material is a hydrophilic polyester chip, or a mixture of a hydrophilic polyester masterbatch and a polyester chip;
[0029] The preparation process of the hydrophilic polyester chips or hydrophilic polyester masterbatch is as follows: after the coated modified inorganic nano functional powder is blended with polyester, the mixture is extruded and granulated by a twin-screw extruder, wherein the temperatures of the first to seventh zones of the twin-screw extruder are 230-240°C, 250-260°C, 260-270°C, 260-270°C, 250-260°C, 250-260°C, 250-260°C, 250-260°C, respectively, the die temperature is 250-260°C, and the screw speed is 380-420r / min;
[0030] The melt index of the hydrophilic polyester chips at 285°C and 1.2kg is 390-450g / 10min; the content of the modified inorganic nano-functional powder coated in the hydrophilic polyester masterbatch is 40-50wt%, and the melt index of the hydrophilic polyester masterbatch at 285°C and 1.2kg is 530-570g / 10min.
[0031] In the method for preparing a hydrophilic polyester melt-blown nonwoven fabric as described above, the drying temperature is 140-160° C. and the drying time is 6-8 hours.
[0032] The method for preparing a hydrophilic polyester melt-blown nonwoven fabric as described above comprises the following steps during melt spinning: single screw extrusion, metering by a metering pump, melt filtering, and melt ejection through a die head;
[0033] The process parameters of melt spinning include: screw zone 1 temperature 270-290°C, screw zone 2 temperature 270-290°C, screw zone 3 temperature 280-300°C, screw zone 4 temperature 280-300°C, metering pump temperature 280-300°C, filtration zone temperature 280-300°C, die zone 1 temperature 280-300°C, die zone 2 temperature 280-300°C, die zone 3 temperature 280-300°C, die zone 4 temperature 280-300°C.
[0034] In the method for preparing a hydrophilic polyester melt-blown nonwoven fabric as described above, during receiving molding, the receiving distance is 15-20 cm.
[0035] A method for preparing a hydrophilic polyester melt-blown nonwoven fabric as described in any of the above items, wherein the hydrophilic polyester melt-blown nonwoven fabric has a water contact angle of 0-3°, a water absorption rate of ≥180%, a water droplet diffusion time of ≤1.5s, a wicking height of ≥120mm, and a complete wetting time of <3s.
[0036] Beneficial effects:
[0037] (1) The coated modified inorganic nano-functional powder used in the preparation method of the present invention contains hydrophilic hyperbranched polyester. The hydrophilic hyperbranched polyester as a hyperbranched polymer can produce a lubricating effect in the polyester substrate, improve the fluidity of the polyester substrate, and increase the melt index of the polyester substrate. Under the action of hot air traction, it can be effectively stretched to obtain finer and more uniform fibers, and complete the crystallization orientation of the fibers, thereby improving the breaking strength of the polyester melt-blown nonwoven fabric.
[0038] (2) The fiber surface of the hydrophilic polyester melt-blown nonwoven fabric of the present invention contains a high content of polar groups, which can enhance the adsorption of water molecules on the fiber surface and improve the hydrophilicity of the polyester melt-blown nonwoven fabric. In addition, the coated modified inorganic nano-functional powder forms a large number of protrusions on the fiber surface, and a large number of grooves are formed between the protrusions on the same fiber surface, which is conducive to the rapid spreading of water on the fiber surface. A large number of capillary-like channels are formed between the protrusions of different fibers, which is conducive to the rapid conduction of water, thereby enhancing the hydrophilicity and moisture conductivity of the polyester melt-blown nonwoven fabric. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a fiber SEM photograph of the hydrophilic polyester melt-blown nonwoven fabric prepared in Example 1 of the present invention.
[0040] Figure 2 This is a fiber SEM photograph of the hydrophilic polyester melt-blown nonwoven fabric prepared in Example 2 of the present invention.
[0041] Figure 3 This is a fiber SEM photograph of the hydrophilic polyester melt-blown nonwoven fabric prepared in Example 3 of the present invention.
[0042] Figure 4 This is a fiber SEM photograph of the hydrophilic polyester melt-blown nonwoven fabric prepared in Example 4 of the present invention.
[0043] Figure 5 This is a fiber SEM photograph of the hydrophilic polyester melt-blown nonwoven fabric prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0045] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0046] (1) Melt index: tested in accordance with GB / T 3682.2-2018, test conditions: temperature 285°C, load 1.2 kg.
[0047] (2) Water contact angle: The test was conducted using a Taishuo TC-A3 water drop angle tester.
[0048] (3) Water absorption: Test according to the water absorption test method in 8.1 of GB / T 21655.1-2023.
[0049] (4) Water droplet diffusion time: Tested in accordance with 8.2 Water droplet diffusion time in GB / T 21655.1-2023.
[0050] (5) Wicking height: Tested in accordance with 8.4 Wicking height in GB / T 21655.1-2023.
[0051] (6) Complete wetting time: Use a sampler to take a sample of 100 cm in an area 20 cm away from the edge of the fabric. 2 Take a round sample and take a glass water tank with a diameter of 30 cm. Fill it with deionized water to a depth of 10 cm. Place the round sample horizontally on the water surface and start timing at the same time. Observe carefully until the color of the sample surface becomes completely dark. It is determined to be completely infiltrated. Stop timing and record the reading as t. Repeat the test 3 times. The arithmetic mean is the complete infiltration time.
[0052] Example 1
[0053] A method for preparing a hydrophilic polyester melt-blown nonwoven fabric, the specific steps are as follows:
[0054] (1) Preparation of raw materials;
[0055] Polyol: 1,1,1-trimethylolpropane;
[0056] Polyacid: 2-hydroxysuccinic acid;
[0057] Catalyst: 4-methylbenzenesulfonic acid;
[0058] Nitrogen;
[0059] Sodium dimethyl 5-sulfonate isophthalate;
[0060] Coupling agent: γ-aminopropyltriethoxysilane;
[0061] Inorganic nanopowder: titanium dioxide, with an average particle size of 80nm;
[0062] Polyester chips: the manufacturer is Yizheng Chemical Fiber, brand FG600;
[0063] (2) preparing coupling agent-modified inorganic nanopowder and hydrophilic hyperbranched polyester respectively;
[0064] The preparation process of the coupling agent modified inorganic nanopowder is as follows: adding the coupling agent and the inorganic nanopowder into a high-speed blender with a rotation speed of 2800 r / min, reacting at 95°C for 2.5 hours, and obtaining the coupling agent modified inorganic nanopowder, wherein the mass of the coupling agent is 4.2% of the mass of the inorganic nanopowder;
[0065] The preparation process of hydrophilic hyperbranched polyester is as follows:
[0066] (a) Add polyol, polyacid and catalyst into a reaction kettle, react at 150°C for 4.5 hours under nitrogen protection, and stir at a speed of 300 r / min during the reaction;
[0067] (b) adding sodium 5-sulfonate dimethyl isophthalate to the reaction kettle and continuing the reaction for 1.5 hours;
[0068] (c) cooling to 105° C., evacuating the reactor to a vacuum degree of 75 Pa for 1 hour to remove unreacted raw materials in the reactor, discharging, cooling, and crushing to obtain a hydrophilic hyperbranched polyester;
[0069] The molar ratio of polyol, polyacid, sodium dimethyl 5-sulfonate isophthalate and catalyst is 1:1.1:0.35:0.002;
[0070] (3) Preparation of coated modified inorganic nano-functional powders;
[0071] The hydrophilic hyperbranched polyester and the coupling agent modified inorganic nano powder were reacted at a temperature of 155°C and a stirring speed of 2400 rpm for 1.2 hours, and the coated modified inorganic nano functional powder was obtained after discharging, cooling, crushing, and air flow crushing. The D50 particle size of the coated modified inorganic nano functional powder was 120 nm, and the mass ratio of the hydrophilic hyperbranched polyester to the coupling agent modified inorganic nano powder was 1:2;
[0072] (4) Preparation of hydrophilic polyester chips;
[0073] The coated modified inorganic nano-functional powder is blended with polyester chips, and then extruded and granulated by a twin-screw extruder to obtain hydrophilic polyester chips; wherein the temperatures of the first to seventh zones of the twin-screw extruder are 230°C, 250°C, 260°C, 260°C, 250°C, 250°C, 250°C, 250°C, respectively, the die temperature is 250°C, and the screw speed is 420r / min;
[0074] The content of the coated modified inorganic nano-functional powder in the hydrophilic polyester chips is 9wt%, and the melt index of the hydrophilic polyester chips at 285°C and 1.2kg is 420g / 10min;
[0075] (5) Preparation of hydrophilic polyester melt-blown nonwoven fabric;
[0076] The process flow is: hydrophilic polyester chips are used as raw materials for drying → melt spinning → hot air drawing → roller receiving and forming, and the hydrophilic polyester melt-blown nonwoven fabric is obtained, and a convex structure is formed on the fiber surface, such as Figure 1 As shown;
[0077] During melt spinning, single screw extrusion, metering by metering pump, melt filtering, and melt ejection through die head are performed in sequence;
[0078] The drying temperature is 150°C and the drying time is 7.5h;
[0079] The process parameters of melt spinning are as follows: screw zone 1 temperature is 280°C, screw zone 2 temperature is 280°C, screw zone 3 temperature is 290°C, screw zone 4 temperature is 290°C, metering pump temperature is 290°C, filtration zone temperature is 290°C, die zone 1 temperature is 290°C, die zone 2 temperature is 290°C, die zone 3 temperature is 290°C, and die zone 4 temperature is 290°C;
[0080] The hot air temperature is 335°C and the drafting air pressure is 0.3MPa;
[0081] The receiving distance is 18cm.
[0082] The fiber diameter range of the finally prepared hydrophilic polyester melt-blown nonwoven fabric is 2-4 μm, and the average diameter is 2.5 μm; the water contact angle of the hydrophilic polyester melt-blown nonwoven fabric is 1.5°, the water absorption rate is 216%, the water droplet diffusion time is 1.0 s, the wicking height is 143 mm, and the complete wetting time is 2.1 s.
[0083] Example 2
[0084] A method for preparing a hydrophilic polyester melt-blown nonwoven fabric, the specific steps are as follows:
[0085] (1) Preparation of raw materials;
[0086] Polyol: The polyol is 3,5-dihydroxytoluene;
[0087] Polyacid: phthalic acid and phenylmalonic acid, the molar ratio of the two is 1:1;
[0088] Catalyst: 4-methylbenzenesulfonic acid;
[0089] Nitrogen;
[0090] Sodium dimethyl 5-sulfonate isophthalate;
[0091] Coupling agent: The coupling agent is γ-aminopropyltrimethoxysilane;
[0092] Inorganic nanopowder: titanium dioxide, with an average particle size of 60nm;
[0093] Polyester chips: the manufacturer is Yizheng Chemical Fiber, brand FG600;
[0094] (2) preparing coupling agent-modified inorganic nanopowder and hydrophilic hyperbranched polyester respectively;
[0095] The preparation process of the coupling agent modified inorganic nanopowder is as follows: adding the coupling agent and the inorganic nanopowder into a high-speed blender with a rotation speed of 2500r / min, reacting at 80°C for 3h, and obtaining the coupling agent modified inorganic nanopowder, wherein the mass of the coupling agent is 3.5% of the mass of the inorganic nanopowder;
[0096] The preparation process of hydrophilic hyperbranched polyester is as follows:
[0097] (a) Add polyol, polyacid and catalyst into a reaction kettle, react at 150°C for 4 hours under nitrogen protection, and stir during the reaction at a speed of 400 r / min;
[0098] (b) adding sodium 5-sulfonate dimethyl isophthalate to the reaction kettle and continuing the reaction for 1.2 hours;
[0099] (c) cooling to 110° C., evacuating, and controlling the vacuum degree in the reactor to 70 Pa for 0.75 h to remove unreacted raw materials in the reactor, discharging, cooling, and crushing to obtain a hydrophilic hyperbranched polyester;
[0100] The molar ratio of polyol, polyacid, sodium dimethyl 5-sulfonate isophthalate and catalyst is 1:1.05:0.2:0.001;
[0101] (3) Preparation of coated modified inorganic nano-functional powders;
[0102] The hydrophilic hyperbranched polyester and the coupling agent modified inorganic nano powder were reacted at a temperature of 140°C and a stirring speed of 3000 rpm for 2 hours, and the coated modified inorganic nano functional powder was obtained after discharging, cooling, crushing, and air flow crushing. The D50 particle size of the coated modified inorganic nano functional powder was 110 nm, and the mass ratio of the hydrophilic hyperbranched polyester to the coupling agent modified inorganic nano powder was 1:1.5;
[0103] (4) Preparation of hydrophilic polyester chips;
[0104] The coated modified inorganic nano-functional powder is blended with polyester chips, and then extruded and granulated by a twin-screw extruder to obtain hydrophilic polyester chips; wherein the temperatures of zones 1 to 7 of the twin-screw extruder are 235°C, 255°C, 265°C, 265°C, 255°C, 255°C, 255°C, respectively, the die temperature is 255°C, and the screw speed is 400r / min;
[0105] The content of the coated modified inorganic nano-functional powder in the hydrophilic polyester chips is 8wt%, and the melt index of the hydrophilic polyester chips at 285°C and 1.2kg is 390g / 10min;
[0106] (5) Preparation of hydrophilic polyester melt-blown nonwoven fabric;
[0107] The process flow is: drying the hydrophilic polyester chips as raw materials → melt spinning → hot air drawing → roller receiving and forming, and the hydrophilic polyester melt-blown nonwoven fabric is obtained, and a convex structure is formed on the fiber surface, such as Figure 2 As shown;
[0108] During melt spinning, single screw extrusion, metering by metering pump, melt filtering, and melt ejection through die head are performed in sequence;
[0109] The drying temperature is 145°C and the drying time is 8h;
[0110] The process parameters of melt spinning are as follows: screw zone 1 temperature is 290°C, screw zone 2 temperature is 290°C, screw zone 3 temperature is 300°C, screw zone 4 temperature is 300°C, metering pump temperature is 300°C, filtration zone temperature is 300°C, die zone 1 temperature is 300°C, die zone 2 temperature is 300°C, die zone 3 temperature is 300°C, and die zone 4 temperature is 300°C;
[0111] The hot air temperature is 340℃ and the drafting air pressure is 0.25MPa;
[0112] The receiving distance is 15cm.
[0113] The fiber diameter range of the finally prepared hydrophilic polyester melt-blown nonwoven fabric is 2-5 μm, and the average diameter is 2.9 μm; the water contact angle of the hydrophilic polyester melt-blown nonwoven fabric is 2.2°, the water absorption rate is 188%, the water droplet diffusion time is 1.3s, the wicking height is 126mm, and the complete wetting time is 2.8s.
[0114] Comparative Example 1
[0115] A method for preparing a polyester meltblown nonwoven fabric is basically the same as that of Example 2, except that in step (4), the content of the coated modified inorganic nano-functional powder in the hydrophilic polyester chips is 6 wt%.
[0116] The final polyester melt-blown nonwoven fabric had a water contact angle of 18.5°, a water absorption rate of 124%, a water droplet diffusion time of 5.7 s, a wicking height of 78 mm, and a complete wetting time of 10.6 s.
[0117] Comparing Example 2 with Comparative Example 1, it can be seen that the hydrophilicity of the polyester melt-blown nonwoven fabric of Comparative Example 1 is significantly reduced. This is because the content of the coated modified inorganic nano-functional powder in the hydrophilic polyester chips is reduced. On the one hand, the content of the hydrophilic component introduced into the polyester matrix is reduced, affecting the hydrophilicity of the polyester melt-blown nonwoven fabric; on the other hand, a multi-protruding rough structure cannot be formed on the surface of the nonwoven fabric fiber, further affecting the hydrophilicity and the diffusion of water in the fiber / fabric.
[0118] Comparative Example 2
[0119] A method for preparing a polyester meltblown nonwoven fabric is basically the same as that of Example 2, except that the parameters of hot air drawing in step (5) are changed so that the fiber diameter of the polyester meltblown nonwoven fabric ranges from 3 to 6 μm and the average diameter is 4.2 μm.
[0120] The final polyester melt-blown nonwoven fabric had a water contact angle of 5.8°, a water absorption rate of 143%, a water droplet diffusion time of 3.2 s, a wicking height of 92 mm, and a complete wetting time of 7.9 s.
[0121] Comparing Example 2 with Comparative Example 2, it can be seen that the hydrophilicity and water diffusivity of the polyester meltblown nonwoven fabric of Comparative Example 2 are reduced. This is because the fibers are not fully stretched, resulting in a coarser fiber diameter and a decrease in the proportion of hydrophilic components exposed on the surface, which affects the hydrophilic effect. At the same time, a multi-protruding rough structure cannot be formed on the fiber surface of the polyester meltblown nonwoven fabric, which further affects the hydrophilicity and the diffusion rate of water in the fiber / fabric.
[0122] Example 3
[0123] A method for preparing a hydrophilic polyester melt-blown nonwoven fabric, the specific steps are as follows:
[0124] (1) Preparation of raw materials;
[0125] Polyol: Polyol is glycerol;
[0126] Polyacid: Phthalic anhydride;
[0127] Catalyst: 4-methylbenzenesulfonic acid;
[0128] Nitrogen;
[0129] Sodium dimethyl 5-sulfonate isophthalate;
[0130] Coupling agent: The coupling agent is 3-glycidyloxypropyltriethoxysilane;
[0131] Inorganic nanopowder: silicon dioxide, average particle size 50nm;
[0132] Polyester chips: the manufacturer is Yizheng Chemical Fiber, brand FG650;
[0133] (2) preparing coupling agent-modified inorganic nanopowder and hydrophilic hyperbranched polyester respectively;
[0134] The preparation process of the coupling agent modified inorganic nanopowder is as follows: the coupling agent and the inorganic nanopowder are added into a high-speed blender with a rotation speed of 2750r / min, and reacted at 100°C for 2h to obtain the coupling agent modified inorganic nanopowder, wherein the mass of the coupling agent is 3% of the mass of the inorganic nanopowder;
[0135] The preparation process of hydrophilic hyperbranched polyester is as follows:
[0136] (a) Add polyol, polyacid and catalyst into a reaction kettle, react at 140°C for 3 h under nitrogen protection, and stir at a speed of 500 r / min;
[0137] (b) adding sodium 5-sulfonate dimethyl isophthalate to the reaction kettle and continuing the reaction for 1 hour;
[0138] (c) cooling to 100° C., evacuating the reactor, and controlling the vacuum degree in the reactor to 65 Pa for 0.5 h to remove the unreacted raw materials in the reactor, discharging, cooling, and crushing to obtain a hydrophilic hyperbranched polyester;
[0139] The molar ratio of polyol, polyacid, sodium dimethyl 5-sulfonate isophthalate and catalyst is 1:1.2:0.4:0.002;
[0140] (3) Preparation of coated modified inorganic nano-functional powders;
[0141] The hydrophilic hyperbranched polyester and the coupling agent modified inorganic nano powder were reacted at a temperature of 150°C and a stirring speed of 2800 rpm for 1.5 hours, and the coated modified inorganic nano functional powder was obtained after discharging, cooling, crushing, and air flow crushing. The D50 particle size of the coated modified inorganic nano functional powder was 80 nm, and the mass ratio of the hydrophilic hyperbranched polyester to the coupling agent modified inorganic nano powder was 1:1;
[0142] (4) Preparation of hydrophilic polyester chips;
[0143] The coated modified inorganic nano-functional powder is mixed with polyester chips, and then extruded and granulated by a twin-screw extruder to obtain hydrophilic polyester chips; wherein the temperatures of the first to seventh zones of the twin-screw extruder are 240°C, 260°C, 270°C, 270°C, 260°C,
[0144] 260℃, 260℃, die head temperature is 260℃, screw speed is 380r / min;
[0145] The content of the coated modified inorganic nano-functional powder in the hydrophilic polyester chips is 10wt%, and the melt index of the hydrophilic polyester chips at 285°C and 1.2kg is 450g / 10min;
[0146] (5) Preparation of hydrophilic polyester melt-blown nonwoven fabric;
[0147] The process flow is: drying the hydrophilic polyester chips as raw materials → melt spinning → hot air drawing → roller receiving and forming, and the hydrophilic polyester melt-blown nonwoven fabric is obtained, and a convex structure is formed on the fiber surface, such as Figure 3 As shown;
[0148] During melt spinning, single screw extrusion, metering by metering pump, melt filtering, and melt ejection through die head are performed in sequence;
[0149] The drying temperature is 140°C and the drying time is 8h;
[0150] The process parameters of melt spinning are as follows: screw zone 1 temperature is 270°C, screw zone 2 temperature is 270°C, screw zone 3 temperature is 280°C, screw zone 4 temperature is 280°C, metering pump temperature is 280°C, filtration zone temperature is 280°C, die zone 1 temperature is 280°C, die zone 2 temperature is 280°C, die zone 3 temperature is 280°C, and die zone 4 temperature is 280°C;
[0151] The hot air temperature is 330℃ and the drafting air pressure is 0.3MPa;
[0152] The receiving distance is 15cm.
[0153] The fiber diameter of the hydrophilic polyester melt-blown nonwoven fabric finally prepared ranges from 1 to 3 μm, with an average diameter of 2.1 μm; the water contact angle of the hydrophilic polyester melt-blown nonwoven fabric is 0°, the water absorption rate is 260%, the water droplet diffusion time is 0.5 s, the wicking height is 166 mm, and the complete wetting time is 1.5 s.
[0154] Comparative Example 3
[0155] A method for preparing a polyester meltblown nonwoven fabric is basically the same as that of Example 3, except that in step (3), the D50 particle size of the coated modified inorganic nano-functional powder is 70 nm.
[0156] The final polyester melt-blown nonwoven fabric had a water contact angle of 2.8°, a water absorption rate of 178%, a water droplet diffusion time of 2.1 s, a wicking height of 120 mm, and a complete wetting time of 4.3 s.
[0157] By comparing Comparative Example 3 with Example 3, it can be seen that the hydrophilicity and water diffusivity of the polyester melt-blown nonwoven fabric of Comparative Example 3 are reduced to a certain extent, and the effect on water diffusivity is more obvious. This is because the particle size of the coated modified inorganic nano-functional powder is reduced, and a good convex structure cannot be formed on the fiber surface, thereby affecting the diffusion and spreading of water on the surface of the polyester melt-blown nonwoven fabric.
[0158] Example 4
[0159] A method for preparing a hydrophilic polyester melt-blown nonwoven fabric, the specific steps are as follows:
[0160] (1) Preparation of raw materials;
[0161] Polyol: Pentaerythritol;
[0162] Polyacid: 9,10-dihydro-9-oxa-10-phosphophenanthrene-succinic acid, CAS No. 63562-33-4, alias: flame retardant DDP;
[0163] Catalyst: 4-methylbenzenesulfonic acid;
[0164] Argon;
[0165] Sodium dimethyl 5-sulfonate isophthalate;
[0166] Coupling agent: γ-aminopropyltrimethoxysilane;
[0167] Inorganic nanopowder: silicon dioxide, average particle size 90nm;
[0168] Polyester chips: the manufacturer is Yizheng Chemical Fiber, brand FG600;
[0169] (2) preparing coupling agent-modified inorganic nanopowder and hydrophilic hyperbranched polyester respectively;
[0170] The preparation process of the coupling agent modified inorganic nanopowder is as follows: adding the coupling agent and the inorganic nanopowder into a high-speed blender with a rotation speed of 3000 r / min, reacting at 90° C. for 2.8 hours, and obtaining the coupling agent modified inorganic nanopowder, wherein the mass of the coupling agent is 5% of the mass of the inorganic nanopowder;
[0171] The preparation process of hydrophilic hyperbranched polyester is as follows:
[0172] (a) Add polyol, polyacid and catalyst into a reaction kettle, and react at 145°C for 5 hours under argon protection, accompanied by stirring at a stirring speed of 600 r / min;
[0173] (b) adding sodium 5-sulfonate dimethyl isophthalate to the reaction kettle and continuing the reaction for 2 hours;
[0174] (c) cooling to 120° C., evacuating the reactor to control the vacuum degree in the reactor to 78 Pa for 1 hour to remove the unreacted raw materials in the reactor, discharging, cooling, and crushing to obtain a hydrophilic hyperbranched polyester;
[0175] The molar ratio of polyol, polyacid, sodium dimethyl 5-sulfonate isophthalate and catalyst is 1:1.1:4:0.003;
[0176] (3) Preparation of coated modified inorganic nano-functional powders;
[0177] The hydrophilic hyperbranched polyester and the coupling agent modified inorganic nano powder were reacted at a temperature of 160°C and a stirring speed of 2000 rpm for 1 hour, and the coated modified inorganic nano functional powder was obtained after discharging, cooling, crushing, and air flow crushing. The D50 particle size of the coated modified inorganic nano functional powder was 130 nm, and the mass ratio of the hydrophilic hyperbranched polyester to the coupling agent modified inorganic nano powder was 1:3;
[0178] (4) Preparation of hydrophilic polyester masterbatch;
[0179] The coated modified inorganic nano functional powder is blended with polyester chips, and extruded and granulated by a twin-screw extruder to obtain a hydrophilic polyester masterbatch; wherein the temperatures of the first to seventh zones of the twin-screw extruder are 230°C, 250°C, 260°C, 260°C, 250°C, 250°C, 250°C, 250°C, respectively, the die temperature is 250°C, and the screw speed is 420r / min;
[0180] The content of the coated modified inorganic nano-functional powder in the hydrophilic polyester masterbatch is 50wt%, and the melt index of the hydrophilic polyester masterbatch at 285°C and 1.2kg is 570g / 10min;
[0181] (5) Preparation of hydrophilic polyester melt-blown nonwoven fabric;
[0182] The process flow is as follows: a mixture of hydrophilic polyester masterbatch and polyester chips is dried as raw material → melt spinning → hot air drawing → roller receiving and forming, and a hydrophilic polyester melt-blown nonwoven fabric is obtained, and a convex structure is formed on the fiber surface, such as Figure 4 As shown; in the mixture of hydrophilic polyester masterbatch and polyester chips, the content of coated modified inorganic nano-functional powder is 8wt%;
[0183] During melt spinning, single screw extrusion, metering by metering pump, melt filtering, and melt ejection through die head are performed in sequence;
[0184] The drying temperature is 150°C and the drying time is 8h;
[0185] The process parameters of melt spinning are as follows: screw zone 1 temperature is 290°C, screw zone 2 temperature is 290°C, screw zone 3 temperature is 300°C, screw zone 4 temperature is 300°C, metering pump temperature is 300°C, filtration zone temperature is 300°C, die zone 1 temperature is 300°C, die zone 2 temperature is 300°C, die zone 3 temperature is 300°C, and die zone 4 temperature is 300°C;
[0186] The hot air temperature is 340℃ and the drafting air pressure is 0.15MPa;
[0187] The receiving distance is 20cm.
[0188] The fiber diameter of the hydrophilic polyester melt-blown nonwoven fabric finally prepared ranges from 2 to 5 μm, with an average diameter of 2.8 μm; the water contact angle of the hydrophilic polyester melt-blown nonwoven fabric is 1.8°, the water absorption rate is 196%, the water droplet diffusion time is 1.4 s, the wicking height is 139 mm, and the complete wetting time is 2.5 s.
[0189] Example 5
[0190] A method for preparing a hydrophilic polyester melt-blown nonwoven fabric, the specific steps are as follows:
[0191] (1) Preparation of raw materials;
[0192] Polyol: tris(hydroxyethyl)isocyanurate, CAS No.: 839-90-7;
[0193] Polyacid: 2-hydroxysuccinic acid and 2-carboxyethylphenylphosphinic acid, the molar ratio of the two is 1:1;
[0194] Catalyst: 4-methylbenzenesulfonic acid;
[0195] Argon;
[0196] Sodium dimethyl 5-sulfonate isophthalate;
[0197] Coupling agent: γ-aminopropyltriethoxysilane;
[0198] Inorganic nanopowder: zinc oxide, average particle size is 100nm;
[0199] Polyester chips: the manufacturer is Yizheng Chemical Fiber, brand FG650;
[0200] (2) preparing coupling agent-modified inorganic nanopowder and hydrophilic hyperbranched polyester respectively;
[0201] The preparation process of the coupling agent modified inorganic nanopowder is as follows: adding the coupling agent and the inorganic nanopowder into a high-speed blender with a rotation speed of 3000r / min, reacting at 100°C for 3h, and obtaining the coupling agent modified inorganic nanopowder, wherein the mass of the coupling agent is 4% of the mass of the inorganic nanopowder;
[0202] The preparation process of hydrophilic hyperbranched polyester is:
[0203] (a) Add polyol, polyacid and catalyst into a reaction kettle, and react at 160°C for 4.2 hours under argon protection, accompanied by stirring at a stirring speed of 300 r / min;
[0204] (b) adding sodium 5-sulfonate dimethyl isophthalate to the reaction kettle and continuing the reaction for 2 hours;
[0205] (c) cooling to 115° C., evacuating the reactor, and controlling the vacuum degree in the reactor to 73 Pa for 1 hour to remove the unreacted raw materials in the reactor, discharging, cooling, and crushing to obtain a hydrophilic hyperbranched polyester;
[0206] The molar ratio of polyol, polyacid, sodium dimethyl 5-sulfonate isophthalate and catalyst is 1:1.05:0.35:0.003;
[0207] (3) Preparation of coated modified inorganic nano-functional powders;
[0208] The hydrophilic hyperbranched polyester and the coupling agent modified inorganic nano powder were reacted at a temperature of 145°C and a stirring speed of 2500 rpm for 2 hours, and the coated modified inorganic nano functional powder was obtained after discharging, cooling, crushing, and air flow crushing. The D50 particle size of the coated modified inorganic nano functional powder was 150 nm, and the mass ratio of the hydrophilic hyperbranched polyester to the coupling agent modified inorganic nano powder was 1:3;
[0209] (4) Preparation of hydrophilic polyester masterbatch;
[0210] The coated modified inorganic nano functional powder is blended with polyester chips, and extruded and granulated by a twin-screw extruder to obtain a hydrophilic polyester masterbatch, wherein the temperatures of zones 1 to 7 of the twin-screw extruder are 240°C, 260°C, 270°C, 270°C, 260°C, 260°C, 260°C, respectively, the die temperature is 260°C, and the screw speed is 380r / min;
[0211] The content of the coated modified inorganic nano-functional powder in the hydrophilic polyester masterbatch is 40wt%, and the melt index of the hydrophilic polyester masterbatch at 285°C and 1.2kg is 530g / 10min;
[0212] (5) Preparation of hydrophilic polyester melt-blown nonwoven fabric;
[0213] The process flow is as follows: a mixture of hydrophilic polyester masterbatch and polyester chips is dried as raw material → melt spinning → hot air drawing → roller receiving and forming, and a hydrophilic polyester melt-blown nonwoven fabric is obtained, and a convex structure is formed on the fiber surface, such as Figure 5 As shown; in the mixture of hydrophilic polyester masterbatch and polyester chips, the content of coated modified inorganic nano-functional powder is 10wt%;
[0214] During melt spinning, single screw extrusion, metering by metering pump, melt filtering, and melt ejection through die head are performed in sequence;
[0215] The drying temperature is 160°C and the drying time is 6h;
[0216] The process parameters of melt spinning are as follows: screw zone 1 temperature is 295°C, screw zone 2 temperature is 295°C, screw zone 3 temperature is 300°C, screw zone 4 temperature is 300°C, metering pump temperature is 300°C, filtration zone temperature is 300°C, die zone 1 temperature is 300°C, die zone 2 temperature is 300°C, die zone 3 temperature is 300°C, die zone 4 temperature is 300°C;
[0217] The hot air temperature is 350°C and the drafting air pressure is 0.1MPa;
[0218] The receiving distance is 15cm.
[0219] The fiber diameter range of the finally prepared hydrophilic polyester melt-blown nonwoven fabric is 1-3 μm, and the average diameter is 2.3 μm; the water contact angle of the hydrophilic polyester melt-blown nonwoven fabric is 0.6°, the water absorption rate is 235%, the water droplet diffusion time is 0.8s, the wicking height is 152mm, and the complete wetting time is 1.9s.
Claims
1. A method for preparing a hydrophilic polyester melt-blown nonwoven fabric, characterized in that: The process flow is: raw material drying → melt spinning → hot air traction → roller receiving and forming; The raw material contains 8-10wt% of coated modified inorganic nano functional powder, and the base material of the raw material is polyester; The coated modified inorganic nano functional powder comprises a coupling agent modified inorganic nano powder and a hydrophilic hyperbranched polyester coated on the surface thereof, wherein the coupling agent modified inorganic nano powder contains an amino group or an epoxy group, and the hydrophilic hyperbranched polyester contains a sulfonic acid group; the inorganic nano powder is one of zinc oxide nano powder, silicon dioxide nano powder and titanium dioxide nano powder; The D50 particle size of the coated modified inorganic nano-functional powder is 80-150nm; The preparation process of the coated modified inorganic nano functional powder is as follows: the hydrophilic hyperbranched polyester and the coupling agent modified inorganic nano powder are reacted at a temperature of 140-160° C. and a stirring speed of 2000-3000 rpm for 1-2 hours, and the coated modified inorganic nano functional powder is obtained by discharging, cooling, crushing, and air flow crushing; wherein the mass ratio of the hydrophilic hyperbranched polyester to the coupling agent modified inorganic nano powder is 1:(1-3); During hot air drawing, the hot air temperature is 330-350℃ and the drawing air pressure is 0.1-0.3MPa; The fiber diameter range of hydrophilic polyester meltblown nonwovens is 1-5 μm, with an average diameter of 2-3 μm; The preparation steps of hydrophilic hyperbranched polyester are as follows: (a) Add polyol, polyacid and catalyst 4-methylbenzenesulfonic acid into a reaction kettle, react at 140-160°C for 3-5h under nitrogen or inert gas protection, and stir during the reaction at a stirring speed of 300-600r / min; (b) adding sodium 5-sulfonate dimethyl isophthalate to the reaction kettle and continuing the reaction for 1-2 hours; (c) After cooling to 100-120° C., the vacuum is continuously applied for 0.5-1 h to remove the unreacted raw materials in the reaction kettle, and the reaction kettle is discharged, cooled, and crushed to obtain a hydrophilic hyperbranched polyester; The polyol is one of pentaerythritol, glycerol, 3,5-dihydroxytoluene, 1,1,1-trimethylolpropane or tris(hydroxyethyl)isocyanurate; The polyacid is one or two of 2-hydroxysuccinic acid, phenylmalonic acid, phthalic acid, phthalic anhydride, 9,10-dihydro-9-oxa-10-phosphophananthrene-succinic acid, and 2-carboxyethylphenylphosphinic acid; The molar ratio of the polyol, the polyacid, the sodium dimethyl 5-sulfonate of isophthalate and the catalyst 4-methylbenzenesulfonic acid is 1:(1.05-1.20):(0.2-0.4):(0.001-0.003).
2. The method for preparing a hydrophilic polyester melt-blown nonwoven fabric according to claim 1, characterized in that: The preparation process of the coupling agent modified inorganic nanopowder is as follows: adding the coupling agent and the inorganic nanopowder into a high-speed blender with a rotation speed of 2500-3000 r / min, reacting at 80-100° C. for 2-3 hours, and obtaining the coupling agent modified inorganic nanopowder; The mass of the coupling agent is 3-5% of the mass of the inorganic nano powder, and the coupling agent is one of gamma-aminopropyl triethoxysilane, gamma-aminopropyl trimethoxysilane or 3-glycidyloxypropyl triethoxysilane.
3. The method for preparing a hydrophilic polyester melt-blown nonwoven fabric according to claim 1, characterized in that: The raw material is hydrophilic polyester chips, or a mixture of hydrophilic polyester masterbatch and polyester chips; The preparation process of the hydrophilic polyester chips or hydrophilic polyester masterbatch is as follows: after the coated modified inorganic nano functional powder is blended with polyester, the mixture is extruded and granulated by a twin-screw extruder, wherein the temperatures of the first to seventh zones of the twin-screw extruder are 230-240°C, 250-260°C, 260-270°C, 260-270°C, 250-260°C, 250-260°C, 250-260°C, 250-260°C, respectively, the die temperature is 250-260°C, and the screw speed is 380-420r / min; The melt index of the hydrophilic polyester chips at 285°C and 1.2kg is 390-450g / 10min; the content of the modified inorganic nano-functional powder coated in the hydrophilic polyester masterbatch is 40-50wt%, and the melt index of the hydrophilic polyester masterbatch at 285°C and 1.2kg is 530-570g / 10min.
4. The method for preparing a hydrophilic polyester melt-blown nonwoven fabric according to claim 1, characterized in that: The drying temperature is 140-160℃ and the time is 6-8h.
5. The method for preparing a hydrophilic polyester melt-blown nonwoven fabric according to claim 1, characterized in that: During melt spinning, single screw extrusion, metering by metering pump, melt filtering, and melt ejection through die head are performed in sequence; The process parameters of melt spinning include: screw zone 1 temperature 270-290°C, screw zone 2 temperature 270-290°C, screw zone 3 temperature 280-300°C, screw zone 4 temperature 280-300°C, metering pump temperature 280-300°C, filtration zone temperature 280-300°C, die zone 1 temperature 280-300°C, die zone 2 temperature 280-300°C, die zone 3 temperature 280-300°C, die zone 4 temperature 280-300°C.
6. The method for preparing a hydrophilic polyester melt-blown nonwoven fabric according to claim 1, characterized in that: When receiving molding, the receiving distance is 15-20cm.
7. A method for preparing a hydrophilic polyester melt-blown nonwoven fabric according to any one of claims 1 to 6, characterized in that: The water contact angle of the hydrophilic polyester meltblown nonwoven fabric is 0-3°, the water absorption rate is ≥180%, the water droplet diffusion time is ≤1.5s, the wicking height is ≥120mm, and the complete wetting time is <3s.
Citation Information
Patent Citations
Preparation method of hydrophilic PET melt-blown material
CN114381860A
Polylactic acid / hyperbranched polyesteramide / nanometer silica ternary composite material and preparation method thereof
CN101570625A
Nanofiber multi-component compound silky non-woven fabric and manufacturing method thereof
CN110578208A